Factors Affecting Maintenance of Buildings in Petroleum Training Institute, Uwvie and Delta State University Abraka, Delta State, Nigeria - M. S. Ibitayo; K. C. Okolie; F. O. Ezeokoli; P. E. Ogunoh (Archives of Current Research International, 2020)
Aim: The aim of this study is to assess the factors hindering effective maintenance of public buildings in Delta state with a view to establishing common defects in public buildings and significant factors affecting effective maintenance in the study area. Study Design: It was a survey research; the study was affected via literature review and a well-structured questionnaire. Likewise, physical observations were carried out to substantiate the findings of the questionnaire survey. Place and Duration of the Study: The study was conducted in Petroleum Training Institute (P.T.I), Uwvie LGA and Delta State University (DELSU), Ethiope West LGA, in Delta state, Nigeria for a period of 2 years. Methodology: Being survey research, the study employed the use of review of related literature, structured questionnaire, personal survey, and photographs for data collections. The study respondents were selected using purposive sampling technique. Relative Importance Index (RII), mean scores, frequency tables and descriptive statistics were employed for the data analysis. Results: The study found out that the four most significant deficiencies identified include; rising dampness problem (0.8656), cracks on walls (0.8469), unstable foundation (0.8094) and defective plastering and rendering (0.7875) while the three least defects are fungi and small plant attack (0.6313), insects (termite) attack (0.6656) and timber decay (0.7031). The most four significant factors affecting building maintenance is Poor supervision (0.8875) followed by defective construction material, incompetent workforce and non-conformance with the specification with RIIs of 0.8719, 0.8531 and 0.8375 respectively. Conclusion: The study concludes that professionals should focus on teamwork rather than personal competitiveness in ensuring defects free design and construction. Professionals should pay more attention to the possibility of defects occurrence when planning construction projects, critical consideration of factors affecting design and construction defects when planning construction activities, engaging required professionals at every stage of the construction process, and strict monitory and supervision of construction works among others are recommended.